The Use of Lausanne Trilogue Play in Three Cases of Gastroschisis Diagnosed during Pregnancy - Pellizzoni, Sandra; Tripani, Antonella; Miscioscia, Marina; Giuliani, Rosella; Clarici, Andrea (Frontiers in Psychology, 2017)
From pregnancy to the first years of a child’s life, families develop and increase representations and interactive competences towards the child. Prenatal diagnosis of a severe fetus’ defect could profoundly alter the parental perception and development of these representations. The aim of the study was to evaluate triadic interactions in families, whose baby was prenatally diagnosed with severe gastroschisis. Three families took part in the preliminary case study, which was carried out when the babies were 6 months old. The Lausanne Trilogue Play shows that prenatal diagnosis of fetal malformation may affect family triadic interactions as follows: a) parents, especially mothers, tend to be intrusive during the play; b) parents presents maladjustments in the child stimulations, especially during the third part, when both parents have to simultaneously interact with the baby; c) parents experience difficulties in creating a space that allows them to communicate directly with each other, leaving the child in a peripheral position. Observational data and clinical implications are discussed.